IMPROVING THE QUALITY OF RICE THROUGH THE PROCESS OF PARBOILED GRAIN TO BE HEALTHY RICE - Eko Priyantono; Sulfianti Sulfianti; Risman Risman (AGROLAND The Agricultural Sciences Journal (e-Journal), 2021)
Rice is one of the staple food in Indonesia which is easy to serve and contain high level carbohydrate, thus influenced the daily activities and human health. The aim of this research is producing low glucose healthy parboiled rice and obtaining the chemical content of Mekongga parboiled rice. This research was held Chemistry Laboratory of Mathematics and Natural Science Faculty, Tadulako University. This research used Mekongga parboiled rice which used completely randomized design with one factor, i.e. kind of treatments, P1 (water soaking with 300 C + steaming for 20 min), P2 (water soaking with 400 C + steaming for 20 min), P3 (water soaking with 500 C + steaming for 20 min), P4 (without water soaking + steaming for 20 min), P5 (without treatment (Control)). Water content, ash content, starch content and sugar reduction were observed in this research. Water soaking with 300 C + steaming for 20 min treatment showed the best result if compared with other treatments in water content level (9.28%), ash content (0.798%), starch content (65.71%), sugar reduction (0.71%), and amylose (23.75%).